MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA MELALUI MODEL KOOPERATIF TWO STAY TWO STRAY (TSTS) TAHUN PELAJARAN 2019/2020 - Mohamad Hadi Susanto (Jurusan Pendidikan MIPA FKIP Universitas Jember, 2020)
Abstract: The success of a lesson can be measured by the achievement of student learning outcomes. Based on the preliminary test, it was found that 22 students (73.3%) were still under the KKM or who scored below 70. To improve learning outcomes, in this study the Two Stay Two Stray (TSTS) cooperative model was used. This type of research is classified as Classroom Action Research (PTK) with the implementation stages referring to the Kemmis and Taggart models. This research was planned in two cycles, including planning, action, observation and reflection. The subjects of this study were students of class VIIB Bangsalsari Junior High School 2019/2020, totaling 30 students. The test and observation method was used for data collection techniques, while the data analysis technique used comparative descriptive analysis (comparison) by comparing the results of pre-cycle, cycle 1 and cycle 2 and was calculated using a simple statistical formula. The results showed that the students' average score in the pre-cycle, cycle I and cycle II was 57.03; 71.97; and 85.57. Completeness of learning outcomes increased from 26.67% (8 of 30 children); 66.67% (20 of 30 children) and 90.00% (27 of 30 children). It can be concluded that the learning outcomes of class VIIB students of SMPN 3 Bangsalsari for the 2019/2020 academic year through the TSTS cooperative model can improve. Kata Kunci: Learning Outcome, cooperative Model, Two Stay Two Stray